855 Dermal exposure to diisocyanates: development and validation of an analytical method for accurately assessment of very low levels of exposure. (24th April 2018) - Duca, Radu-Corneliu; Creta, Matteo; Poels, Katrien; Godderis, Lode; Vanoirbeek, Jeroen
Abstract : Introduction: Dermal exposure to sensitizers such as diisocyanate have been described to promote the development of asthma in later stages when respiratory occupational exposure occurs. Therefore, we developed a reliable, sensitive and validated methodology based on dermal patches to assess skin exposure to diisocyanates. Methods: An UPLC-Unispray-MS/MS method was established and validated in order to reach very low levels of detection. Custom-made dermal patches were developed in order to allow optimal sampling of diisocyanates. Their sampling capability was evaluated in a controlled environment test-chamber were patches were exposed to increasing concentrations of diisocyanates. Result: The UPLC-MS/MS method using a Unispray ionisation source, based on supercritical fluids ionisation and Coanda effect, allowed reaching very low levels of detection (LoD=1 pg/mL) for all the targeted compounds (i.e. 4, 4-MDI, 2, 4-MDI, 2, 6-TDI, 2, 4-TDI, 1, 6-HDI, and IPDI). Due to the high sensitivity of the analytical method, very low levels of diisocyanates (i.e. 25 pg/patch) are detected on the custom-made dermal patches. Furthermore, the patches allowed the sampling of a broad range of concentration levels (from 5 pg/cm 2 to 5 ng/cm 2 ), which have been correlated with the air levels from the controlled environment chamber-test. Discussion: We succeeded to develop a method to assess dermal exposure to diisocyanates. Field studies are now necessary to further evaluate the suitability of the custom-made patches, as well as to relate low levels of exposure and potential health outcomes.